This bridge will not be gray - Eggers, Dave (McSweeney's, 2015)
"The Golden Gate Bridge is the most famous bridge in the world. It is also, not entirely coincidentally, the world's only bright-orange bridge. But it wasn't supposed to be that way. In this book, fellow bridge-lovers Dave Eggers and Tucker Nichols tell the story of how it happened - how a bridge that some people wanted to be red and white, and some people wanted to be yellow and black, and most people wanted simply to be gray, instead became, thanks to the vision and stick-to-itiveness of a few peculiar architects, one of the most memorable man-made objects ever created."--provided by Amazon.com.